A Clinical Approach to Arterial Ischemic Childhood Stroke: Increasing Knowledge over the Last Decade - Steinlin, Maja (Neuropediatrics, 2012)
Childhood stroke is increasingly being recognized as an important burden not only for affected children and families, but also for socioeconomic reasons. A primary problem is delayed diagnosis, due to the many mimics of childhood stroke, and the variety of manifesting symptoms. The most important is hemiparesis (with/without dysphasia or facial palsy), but ataxia, seizures, and many more are also possible. Suspicion of stroke has to be ascertained by neuroimaging, gold standard being (diffusion weighted) magnetic resonance. Risk factors are multiple, but their presence might help to increase the suspicion of stroke. The most important factors are infectious/parainfectious etiologies, frequently possibly manifesting by transient focal cerebral arteriopathy (FCA). Cardiological underlying problems are the second most important. Arteriopathies can be detected in about half of the children, besides FCA and dissection and MoyaMoya disease are the most important. Hereditary coagulopathies increase the risk of stroke. There is still a controversy on best treatment in children: platelet antiaggregation and heparinization are used about equally. Thrombolysis is being discussed increasingly. Severity of symptoms at manifestation and on follow-up are not less significant in children than in young adults. About two-third of the children have significant residual neurological problems and a majority cognitive and behavior problems.
Keywords: childhood stroke; risk factors; etiology; treatment; manifestation; outcome